Rancang Bangun Game Bersepeda Berbasis 3D Map Tersinkronisasi Dengan Sistem Kendali Gyroscope Dan Infrared - Abdul Latif Priyadi; Sutrisno Sutrisno; Faisal Rahutomo (Jurnal FORTECH, 2022)
Body health must be maintained by every individual from children to the elderly. In order for the health of the body to be in prime condition, it takes sports activity. One of the sports favored by children is cycling. Cycling is a good sport because it moves many parts of the body, from the hands on the wheel and feet to pedaling. However, some children are lazy and get bored easily when exercising because there is no motivation. Some children prefer to spend their time playing games, so a tool is needed as a means of sport that is packaged in a game to make it interesting. To form a game that resembles bicycle movements, tools can be made using ESP8266, MPU6050 as steering wheel control sensors, and infrared sensors as pedal controls. This tool will be input into the game with serial communication via a USB cable. Games with bicycle themes are made using Unity 3D coded with Visual Studio Code. The results of tests carried out using the black box method, tools and games can run according to design, starting from connecting hardware to software, calibrating, controlling games with tools, and running gameplay on games. Testing was also carried out using the User Acceptance Test (UAT) method with 60 respondents and obtained an overall score of 94.11%.